Youth in the Northern Cape, South Africa, Engage in High-risk Behaviors Such as Drinking and Using Drugs - (:unkn) unknown (My University, 2023)
The objective of the study was to investigate, from a qualitative standpoint, how young people in the Northern Cape Province of South Africa perceive risky behaviors, especially those connected to and including the use of alcohol and other drugs. Adolescent alcohol usage is linked to several risky behaviors, such as harmful alcohol use, driving while intoxicated, unsafe sex, and aggression. The paper examined various viewpoints on the incidence, effects, and risk factors associated with alcohol consumption among young people in South Africa's Northern Cape Province. Despite the numerous health issues linked to heavy drinking, alcohol is one of the most commonly consumed substances in South Africa. Alcohol abuse among young people is a persistent issue. Many young adults binge drink excessively, which has grave detrimental effects later. In the Northern Cape Province of South Africa, the project aims to understand the factors contributing to adolescent alcoholism. For the study, a qualitative research methodology was used. The participants in the trial in the Northern Cape Province were adolescent drinkers between the ages of 14 and 35. The cultural practices of the participants' reservation communities were well-known to them. Participants revealed varying ideas about what alcohol means and the most effective intervention measures, despite the fact that there was agreement over how common heavy drinking is. Three conundrums were found, indicating that a barrier to lowering problem drinking may be the ambivalence of the community. Discussions are had regarding the implications, restrictions, and directions for further study. Finally, a chronological presentation of the study's findings is made.
Keywords: African Research